Odpowiedzi

Najlepsza Odpowiedź!
2010-03-05T17:28:53+01:00
F(x)=-(x+5)²+9

F(x)=-(x²+10x+25)+9

F(x)=-x²-10x-25+9

F(x)=-x²-10x-16

Δ=100-64=36
√Δ=6

x₁=-8
x₂=-2

y=-(x+2)(x+8)

2010-03-05T17:47:57+01:00
F(x)=-(x+5)²+9
F(x)=-(x²+10x+25)+9
F(x)=-x²-10x-25+9
F(x)=-x²-10x-16

Δ=b²-4ac
a=-1
b=-10
c=-16
Δ=(-10)²-4*(-1)*(-16)=100-4*16=100-64=36
√Δ=6

x₁=(-b-√Δ)/2a=(-(-10)-6)/(-2)=(10-6)/(-2)=4/(-2)=-2
x₂=(-b+√Δ)/2a=(-(-10)+6)/(-2)=(10+6)/(-2)=16/(-2)=-8

y=a(x-x₁)(x-x₂)
y=-1(x-(-2)) (x-(-8))
y=-(x+2)(x+8)